(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This study aims to investigate the impact of data-driven leadership on performance in sports organizations focusing on Najaf’s General Directorate of Youth and Sports in particular Questionnaire (100 questionnaires) on leadership practices of data use and impact on performance of sports organizations was distributed to the staff of the General Directorate of Youth and Sports in Najaf (88) questionnaires were collected, (88) validated questionnaires for statistical analysis, (85) . questions were Smart Analyzed using PLS V.4, the study also found a list of results, the most important of which were: There is a relationship between improving performance, and this is an important finding well. Data-driven leadership is not a magic bullet, but it is a powerful tool that can dramatically improve organizational performance and decision-making. By creating a culture of data consumption, putting data insights to good use, and prioritizing data literacy, leaders can overcome today’s challenging business environment and achieve sustainable success Several recommendations are made, including: Educate employees and stakeholders about the importance of data, its use in order to improve performance and performance.